Nanoengineered Gd3Al2Ga3O12 Scintillation Materials with Disordered Garnet Structure for Novel Detectors of Ionizing Radiation. Issue 4 (6th March 2019) - Korzhik, Mikhail; Alenkov, Vladimir; Buzanov, Oleg; Fedorov, Andrei; Dosovitskiy, Georgy; Grigorjeva, Larisa; Mechinsky, Vitaliy; Sokolov, Peter; Tratsiak, Yauhen; Zolotarjovs, Aleksejs; Dormenev, Valery; Dosovitskiy, Aleksei; et al.
Abstract: The search for engineering approaches to improve the scintillation properties of Gd3 Al2 Ga3 O12 crystals and enable their production technology is of current interest. This crystal, while doped with Ce, is considered a good multi‐purpose scintillation material for detecting gamma‐quanta and neutrons. It is observed that co‐doping with Mg affected intrinsic defects in the crystal structure that create shallow electronic traps. Other point structure defects, which are based on local variations of the crystal stoichiometry, are significantly diminished by use of a co‐precipitated raw material. Nano‐structuring of the raw material enables production of a homogeneous precursor mixture for growing a crystal with minimal evaporation of Ga from the melt. The demonstrated nano‐engineering approach increased the light yield from the crystal by approximately 20%, enabling its applications in well logging. Abstract : A technological approach to control defect formation in Gd3 Al2 Ga3 O12 :Ce crystalline material and minimize their effect on the crystal scintillation properties is successfully implemented. Co‐doping of the crystal with an aliovalent impurity acts as an efficient tool for reducing the crystal structure disordering, while use of co‐precipitated nanostructured raw material diminishes the effect of gallium evaporation from the melt during the crystal growth.